2009
DOI: 10.1111/j.1557-9263.2009.00211.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of color banding, radio tagging, and repeated handling on the condition and survival of Lapwing chicks and consequences for estimates of breeding productivity

Abstract: Color bands and radio tags are widely used to facilitate individual recognition and relocation of precocial chicks in studies of prefledging survival. However, the accuracy of data collected and subsequent estimates of survival rates rely on the assumption that such techniques do not affect the parameters under study. We compared the body condition and survival of color‐banded and radio‐tagged Lapwing (Vanellus vanellus) chicks with noncolor‐banded and nonradio‐tagged individuals using a 10‐year dataset (N= 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 37 publications
(51 reference statements)
0
33
0
Order By: Relevance
“…2009). However, Sharpe et al. (2009) showed that frequent disturbance and repeated handling affect chick body condition and survival probability.…”
Section: Methodsmentioning
confidence: 99%
“…2009). However, Sharpe et al. (2009) showed that frequent disturbance and repeated handling affect chick body condition and survival probability.…”
Section: Methodsmentioning
confidence: 99%
“…Sharpe et al . () found that frequent disturbance associated with tracking and recapturing chicks, rather than the attachment of a tag itself, affected body condition, but that a recapture frequency of greater than 8 days was sufficient to reduce this effect. By following this recommendation the chicks we monitored attained body condition equal to or better than expected for their age, and there was no significant difference in condition between tagged and untagged chicks (Table S8; Beintema , Mason & Smart ).…”
Section: Discussionmentioning
confidence: 99%
“…, Sharpe et al . ). Although two‐way interactions between predator activity variables were biologically plausible, we only included main effects in our models, as including interactions would have resulted in model overspecification due to our relatively small dataset (full model parameters n = 9; binomial datapoints: success/predation n = 133, failure/survival n = 1484; Harrell ).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Although hatchling shorebirds can often be marked using adult-sized leg bands (Sharpe et al 2009), this option is not suitable for young waterfowl (Anseriformes) or rails (Rallidae). Previous methods of marking precocial waterbirds have included colordyeing plumage either before or after hatch (Evans 1951;Eadie and Lyon 1998), web tagging (Alliston 1975), web clipping (Eichhorst 1986), plasticine-filled leg bands (Blums et al 1994), colored nasal-tags (Sugden and Poston 1968), and miniature radio transmitters (Mauser and Jarvis 1991).…”
mentioning
confidence: 99%